2012
DOI: 10.1124/jpet.112.198978
|View full text |Cite
|
Sign up to set email alerts
|

Gs-Coupled Adenosine Receptors Differentially Limit Antigen-Induced Mast Cell Activation

Abstract: Mast cell activation results in the immediate release of proinflammatory mediators prestored in cytoplasmic granules, as well as initiation of lipid mediator production and cytokine synthesis by these resident tissue leukocytes. Allergen-induced mast cell activation is central to the pathogenesis of asthma and other allergic diseases. Presently, most pharmacological agents for the treatment of allergic disease target receptors for inflammatory mediators. Many of these mediators, such as histamine, are released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 67 publications
1
9
1
Order By: Relevance
“… Ryzhov et al (2008b) demonstrated that BMMCs in A 2B AR KO mice display two distinct phenotypes. One effect is enhanced antigen-induced degranulation, consistent with an inhibitory role of A 2B AR in degranulation as reported by Hua et al (2013a) . The other effect observed in A 2B AR KO mice is loss of NECA-induced increases of IL-13 leading to vascular endothelial growth factor (VEGF) secretion.…”
Section: In Vivo Studies Of Degranulationsupporting
confidence: 86%
See 2 more Smart Citations
“… Ryzhov et al (2008b) demonstrated that BMMCs in A 2B AR KO mice display two distinct phenotypes. One effect is enhanced antigen-induced degranulation, consistent with an inhibitory role of A 2B AR in degranulation as reported by Hua et al (2013a) . The other effect observed in A 2B AR KO mice is loss of NECA-induced increases of IL-13 leading to vascular endothelial growth factor (VEGF) secretion.…”
Section: In Vivo Studies Of Degranulationsupporting
confidence: 86%
“…Thus, A 2B AR agonists rather than antagonists can be considered as a therapy for asthma. Hua et al (2013a) reported that the two Gs-coupled A 2A and A 2B ARs differentially limit antigen-induced mast cell activation. By comparing mast cell responses of mice with various combinations of AR KOs, they showed that AR agonists can modulate mast cell degranulation and induction of cytokine production both in vitro and in vivo .…”
Section: In Vivo Studies Of Degranulationmentioning
confidence: 99%
See 1 more Smart Citation
“…A2BR activation limits cells degranulation [84]. The combination of A2AR and A2BR activation is required for the inhibition of cytokine synthesis both in vitro and in vivo [85,86]. MCs isolated from wild type (WT), not A2BR knocked out (KO) mice, release IL-13 and VEGF in response to extracellular ADO, suggesting the role of A2BR in angiogenesis [87].…”
Section: Ado and Mast Cells (Mcs)mentioning
confidence: 99%
“…Both A 2A and A 2B receptors were identified on mouse bone marrow-derived mast cells [ 142 ]. Using knockout mice, it was demonstrated that the inhibition of mast cell degranulation by adenosine in mediated by the A 2B receptor, while the combined action of A 2B and A 2A receptors is responsible for the inhibition of cytokine production [ 143 ]. However, the role of adenosine receptors in mast cell regulation is more complex, since the stimulatory effect of adenosine on the release of angiogenic factors such as vascular endothelial growth factor (VEGF) was shown to involve a cooperation between A 2B and A 3 receptors [ 144 , 145 ].…”
Section: Purinergic Signalling In the Main Subsets Of Immune Cellsmentioning
confidence: 99%